TVET in Nepal: Scope and the Associated Challenges - Koirala, Sambedan (Journal of Training and Development, 2025)
Technical and vocational education and training (TVET) equips individuals with specific skills required for the job market. It also provides a workforce that is needed for employment generation, entrepreneurship, and industrial growth. During the pre-agricultural stage of society, human beings used to practice the on-the-job phenomenon to learn the basic and necessary skills required for survival and cultural continuity. As society changed, vocational education also evolved in the form of formal and informal apprenticeships, oral tradition, and experiential learning. In Nepal, the establishment of the Council for Technical Education and Vocational Training (CTEVT) officially ensured that long and short courses offered by technical schools produce skillful human resources that are needed for the economic growth of the country. Despite the growth in technical schools across the years, this article shows that TVET has not been able to bridge the gap between demand and supply of the workforce. This article has used secondary data to examine the status of population demographics and employment rate and also has explored the enrolment capacity versus actual enrollment in technical schools. In addition, this study has also explored the status of instructors in technical schools. Based on the secondary data, this study concludes that there is a need for a nationwide debate along with a plan of action to improve all aspects of TVET programs if Nepal aims to cultivate self-reliant and self-employed individuals as a way of reducing unemployment in the country.